2004
DOI: 10.1172/jci21083
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical deposition of pathological prion protein PrPSc in muscles of hamsters orally exposed to scrapie

Abstract: Recently, pathological prion protein PrP Sc , the putative key constituent of infectious agents causing transmissible spongiform encephalopathies (TSEs), was found in muscles of rodents experimentally infected with scrapie and in patients with Creutzfeldt-Jakob disease (CJD). For the assessment of risk scenarios originating from these findings (e.g., alimentary transmission of pathogens associated with bovine spongiform encephalopathy [BSE]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…In support of this possibility we found PrPres detectable by IHC at high levels in white fat associated with skeletal muscle in some tg44 mice ( Figure 4 ). In contrast, other groups did not mention seeing PrPres in muscle-associated fat tissue in animals where myocytes themselves were seen to be positive by IHC [13] [20] .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In support of this possibility we found PrPres detectable by IHC at high levels in white fat associated with skeletal muscle in some tg44 mice ( Figure 4 ). In contrast, other groups did not mention seeing PrPres in muscle-associated fat tissue in animals where myocytes themselves were seen to be positive by IHC [13] [20] .…”
Section: Discussionmentioning
confidence: 91%
“…It was also noteworthy that in BSE infected cattle, both spleen and skeletal muscle were negative or extremely low by infectivity testing, suggesting that BSE infected cattle differ from other models in this aspect [7] , [8] . PrPres was also detected by western blot in tongue of hamsters and sheep [13] [15] , skeletal muscles of mice, sheep, and hamsters [12] , [13] , [16] , [17] and cardiac muscle of deer and elk [18] . IHC analysis for PrPres in these tissues was also often positive in myocytes and nerves while fat tissue adjacent to muscle was not noted to be positive [13] [21] .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To accomplish this goal, we monitored prion infection of skeletal muscle in the tongue since prior studies demonstrated that muscle cells of the tongue are susceptible to prion infection (12,22,(31)(32)(33) and since each muscle cell has a single neural synapse, or neuromuscular junction. We demonstrate centrifugal spread of prions from the brain stem to nerve fibers of the tongue, followed by localization to the neuromuscular junction prior to entry into, and replication in, muscle cells.…”
mentioning
confidence: 99%
“…Localization of PrP Sc in the muscle spindles of skeletal muscles in the study was consistent with that of atypical BSE in cattle [ 8 ] and natural scrapie in sheep [ 1 ]. In addition, immunolabeled PrP Sc localized at the terminal nerve endings of myofibrils has been reported in hamsters with scrapie and [ 16 ] in rodent and primate models with C-BSE and CJD, respectively [ 6 , 9 , 17 ].…”
mentioning
confidence: 99%